PENGARUH TEKNOLOGI E-LEARNING DAN PEMBELAJARAN HYBRID TERHADAP EFEKTIVITAS PEMBELAJARAN BAGI MAHASISWA BEKERJA - Amrizal Amrizal; Rika Harman; Erlin Elisa (Ensiklopedia of Journal, 2023)
This study discusses the effectiveness implementation of E-learning and the hybrid learning for students working while studying, almost 4 semesters of students conducting lectures are carried out online, where education managers have started carrying out offline lectures, but all of that not yet fully implemented 100%, several courses that are felt to be conducted face-to-face or offline and there are courses that can be taken online and some are also conducted online and offline which is called hybrid learning. In implementing hybrid learning, there are many obstacles, especially for students with work-while-study status who adjust their work schedules to the class schedule set by the campus. This study uses a quantitative method using generalized samples. The research hypothesis was tested statistically. From the results it was found that the implementation of hybrid learning which was applied to students working status was not effective, but with the existence of an E-learning based teaching information system it has increased learning effectiveness up to 63% contribution, E-learning is very helpful in solving problems from hybrid learning, besides that It is also necessary to attention for the lecture scheduling strategy so that students with a working background can adjust and attend lectures properly.